Nineteenth century research on cell death - Clarke, P.G.H.; Clarke, S. (Experimental Oncology, 2012)
This paper reviews research on cell death in the 19th C. The first report of cell death was by Vogt in 1842, which was remarkably soon after the establishment of the cell theory by Schleiden and Schwann between 1838 and 1842. Initial studies on cell death, including that of Vogt, focused on its occurrence in metamorphosis (Vogt, 1842; Prévost and Lebert, 1844; Weismann, 1863–1866) or in blatant pathology (Virchow, 1858), but as histological techniques improved it was found to be involved in more subtle roles in numerous situations including endochondral ossification (Stieda, 1872), ovarian follicle atresia (Flemming, 1885), cell turnover (Nissen, 1886), the wholesale loss of a population of sensory neurons in fish (Beard, 1889), and the naturally occurring histogenetic death of myocytes (Felix, 1889) and neurons (Collin, 1906). The current categorization of cell death into about three main morphological types has 19th century roots in that apoptosis was well described by Flemming (1885), who called it chromatolysis, and various authors including Noetzel (1895) proposed a threefold classification. This article is part of a Special Issue entitled “Apoptosis: Four Decades Later”.